MHC-II MARKER POTENTIAL LINKED TO MOTILE AEROMONAD SEPTICAEMIA DISEASE RESISTANCE IN AFRICAN CATFISH (Clarias gariepinus) - Rommy Suprapto; Alimuddin Alimudddin; Sri Nuryati; Imron Imron; Huria Marnis; Bambang Iswanto (Indonesian Aquaculture Journal, 2017)
One of the important issues in catfish farming is motile aeromonad septicaemia (MAS) disease caused by the bacterium Aeromonas hydrophila. This study aimed to find the MHC-II marker potential for marker-based selection to generate MAS disease resistance of African catfish. PCR method was applied to identify catfish (body length: 7-8 cm) population that have MHC-II marker. Fish with and without the marker were then challenged by intraperitonially injecting of 0.1 mL/fish with A. hydrophila (105 cfu/mL). The results showed that the survival of fish having MHC-II marker (77.50 ± 4.00%) was higher than that of fish without the marker (53.33 ± 4.77%). Fish carrying MHC-II marker fish has also higher total erythrocytes, total leukocytes, phagocytic activity, and hematocrit levels than that of fish without the marker. The PCR results using specific primer for MHC-II showed a specific DNA band of 426 bp in fish having the marker, while there were no DNA bands in fish without the marker. Results of the PCR analyses showed that the percentage of progenies carrying MHC-II marker was 80%, while progenies from broodstock without the marker was 0%; this indicated that MHC-II marker could be inherited to the offsprings. Thus, the MHC-II marker could be used as a molecular marker of MAS disease resistance catfish.